2008
DOI: 10.1159/000121334
|View full text |Cite
|
Sign up to set email alerts
|

Is Antidepressant Treatment Associated with Reduced Cognitive Decline in Alzheimer’s Disease?

Abstract: Background: Although antidepressant drugs (ATD) are frequently prescribed to patients with Alzheimer’s disease (AD), their effect on cognitive status has been only rarely assessed. Methods: The impact of depressive symptoms and ATD on cognitive status was retrospectively assessed in 72 older AD outpatients with mild-to-moderate cognitive impairment, treated with cholinesterase inhibitors, over a 9-month follow-up. Results: Compared to subjects without baseline depressive symptoms, those with symptoms who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 80 publications
3
33
0
1
Order By: Relevance
“…Mossello et al mentioned that antidepressant treatment would protect cognitive function in depressed older patients with AD [54]. They further suggested that cognitive protection was possibly via a reduction in depressive symptoms after taking antidepressants, while we proposed that antidepressant medication might increase the risk of dementia independent of depression.…”
Section: Discussionmentioning
confidence: 65%
“…Mossello et al mentioned that antidepressant treatment would protect cognitive function in depressed older patients with AD [54]. They further suggested that cognitive protection was possibly via a reduction in depressive symptoms after taking antidepressants, while we proposed that antidepressant medication might increase the risk of dementia independent of depression.…”
Section: Discussionmentioning
confidence: 65%
“…The evidence for cognitive effect of antidepressant drugs is even weaker. Observational data support a reduced cognitive decline associated with antidepressants in patients with AD treated with CIs [Mossello et al 2008] and a pilot clinical trial has shown a beneficial effect of the association between selective serotonin reuptake inhibitors and CIs on functional status and clinical global impression [Mowla et al 2007]. However, taking into account the increased risk of adverse events linked to antidepressant treatment and the high response rate observed with placebo, the use of antidepressants in patients with AD has little support from a QoL perspective, except in the case of severe symptoms.…”
Section: Psychotropic Medicationsmentioning
confidence: 90%
“…In advanced AD, different serotonin receptor agonists show promising effects in enhancing memory and learning capacity according to clinical and animal studies [92,98]. In the same line, administration of serotonin re-uptake inhibitors improved memory function in AD patients [99]. Additionally, deficits in serotonergic innervation, serotonin transporters and tryptophan hydroxylase may contribute to anxiety and changes in waking/sleep cycle seen in AD [100,101].…”
Section: Dorsal Raphe Nucleus and The Serotonergic Systemmentioning
confidence: 99%